Andrew Lim Wei Chin named recipient of Excellence Award of UMPSA Holdings Sdn. Bhd. - Norhidayah, Mohamad (UMPSA, 2024)
GAMBANG, 21 October 2023 - His drive for excellence finally came to fruition when Andrew Lim Wei Chin, 24, was named the recipient of the UMPSA Holdings Excellence Award at the Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA) 18th Convocation Ceremony.